The Lack of Benefit of a Combination of an Angiotensin Receptor Blocker and Calcium Channel Blocker on Contrast-Induced Nephropathy in Patients with Chronic Kidney Disease. (May 2013) - Oguzhan, Nilufer; Cilan, Havva; Sipahioglu, Murat; Unal, Aydin; Kocyigit, Ismail; Kavuncuoglu, Feridun; Arikan, Tamer; Akpek, Mahmut; Elcik, Deniz; Sahin, Omer; Gulme, Ebru; Pala, Cigdem; et al.
<x xml:space="preserve">Abstract</x> Aim: Contrast-induced nephropathy (CIN) is a relatively common and serious complication, which occurs after the administration of contrast materials to patients. Although the pathophysiology of CIN is not exactly understood, ischemia of the medulla, oxidative stress, and direct toxicity of the contrast material are some of the factors that are implicated for the pathogenesis of CIN. To date, the only therapy that reduces the risk of CIN is volume expansion. There are conflicting results about the roles of angiotensin receptor blockers (ARB) and calcium channel blockers (CCB) in studies on CIN. For this reason the aim of this study was to compare the efficiency of the prophylactic use of amlodipine/valsartan plus hydration versus hydration only for the prevention of CIN in patients undergoing coronary angiography (CAG). Patients and methods: We prospectively enrolled 90 patients whose baseline serum creatinine levels were under 2.1 mg/dL and who were scheduled for CAG. Patients were divided into two groups. Group I (n = 45), consisted of patients who received amlodipine/valsartan plus hydration, group II (n = 45) consisted of patients who received only hydration. The patients in group I were given amlodipine/valsartan 5/160 mg once a day for a total of 3 days, starting one day before CAG and continuing on the day of and the day after the procedure. A 1 mL/kg/h sodium chloride infusion was administered for a total of 24 h, starting 12 h before the procedure and 12 h after, in all patients. The baseline serum creatinine (Scre) level was obtained before the procedure and repeated 48 h after. CIN was defined as an increase of ≥0.5 mg/dL or an increase of >25% in baseline Scre on the second day after CAG. Results: The baseline clinical characteristics of the treatment groups were similar. Baseline Scre was 1.13 ± 0.33 in group I and 1.07 ± 0.23 mg/dL in group II (p = 0.31). There was a significant difference between the Scre levels 48 h after CAG between the two groups (1.18 ± 0.33–1.05 ± 0.23) (p = 0.03). The reason for this was the increase of Scre in group I. CIN occurred in 17.8% (8/45) of patients in group I and in 6.7% (3/45) of patients in group II (p = 0.197). In the diabetic subgroup, CIN occurred in 10.5% (2/19) of patients taking amlodipine/valsartan and in none of the patients in group II (p = 0.486). The Mehran scores of the patients who developed CIN were significantly higher than those patients who did not develop CIN. Conclusion: Amlodipine/valsartan therapy plus hydration did not reduce the risk of CIN in chronic kidney disease (CKD) Stage 2 patients who underwent elective CAG using a low-osmolar nonionic contrast medium. This is because there was a decrease in the glomerular filtration rate (GFR) using the Levey Modification of Diet in Renal Disease (MDRD) formula in the amlodipine/valsartan group and CIN occurred at a higher frequency in this group; ARBs and CCBs may be withheld before CAG in high-risk patients.